Pengaruh Terpaan Pemberitaan Timnas Sepak Bola Indonesia terhadap Tingkat Fear of Missing Out (FOMO) pada Pengikut Akun Instagram @timnasindonesia - Nafisah, Kimyatun; Sumardjijati, Sumardjijati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This study aims to determine the effect of exposure to news on the Instagram account @timnasindonesia on the level of Fear of Missing Out (FoMO) in its followers. FoMO is a psychological condition in which individuals feel anxious or worried about missing out on important information that occurs around them, especially in the context of social media. This study uses a quantitative approach with a survey method on 100 respondents who are active followers of the @timnasindonesia account. The sampling technique was carried out by purposive sampling with certain criteria. The research instrument was compiled in the form of a questionnaire using a Likert scale that includes three indicators on the exposure variable (frequency, duration, attention) and three indicators on the FoMO variable (fear, worry, anxiety). Data assistance analysis was carried out using a simple linear regression test with IBM SPSS Statistics 29. The results showed that there was a positive and significant effect between news exposure on FoMO with a regression coefficient value of 0.556, t count of 4.414, and a significance value <0.001. The coefficient of determination (R²) of 0.166 shows that 16.6% of the variation in FoMO can be explained by the news exposure variable.